LAGU MENIDURKAN ANAK PADA MASYARAKAT BANJAR: KAJIAN BENTUK, MAKNA, DAN FUNGSI - Adeliani, Noor (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
This research is intended to find out the form, the meaning and the function of the lyrics of Banjarese Lullabies. The method used is descriptive qualitative using Ricoeur's hermeneutic approach to understand the lyrics in Banjarese Lullabies. This study found that (1) the lyrics of Banjarese Lullabies have two forms; free and bound forms; (2) the meaning of the lyrics of the lyrics of Banjarese Lullabies contains request, prayer, education, introduction of religion, and advice, (3) the function of the lyrics of Banjarese Lullabies are referential function, expressive function, directive function and aesthetic function. This research also indicates that the similar research should be carried out continously to prevent the lyrics of Banjarese Lullabies from extinction.